Spine surgery and complication in familial dysautonomia: a case report - Fava, M.; Ciani, G.; Ghermandi, R.; Cini, C.; Maccaferri, B.; Gasbarrini, A. (Frontiers in Surgery, 2025)
Familial dysautonomia (FD) is an inherited severe congenital disease and a rare syndrome associated with progressive neuronal degeneration throughout life. Among its orthopedic conditions, FD patients have an higher incidence of kyphoscoliosis and osteomyelitis. Due to the rarity of FD and the presence of multiple comorbidities, there are currently no established guidelines for the management of vertebral pathologies associated with FD. Hence, this highlights the importance of sharing the case of our patient. The purpose of our study is to report the case of a 45-year-old patient with FD who underwent multiple spinal surgeries at our clinic, to provide possible indications for the most effective management of this rare condition.